β-Lactam Antibiotics Enhance the Pathogenicity of Methicillin-Resistant Staphylococcus aureus via SarA-Controlled Lipoprotein-Like Cluster Expression - Weilong Shang (American Society for Microbiology, 2019)
ABSTRACT Methicillin-resistant Staphylococcus aureus (MRSA) resists nearly all β-lactam antibiotics that have a bactericidal activity. However, whether the empirically used β-lactams enhance MRSA pathogenicity in vivo remains unclear. In this study, we showed that a cluster of lipoprotein-like genes (lpl, sa2275 to sa2273 [sa2275–sa2273]) was upregulated in MRSA in response to subinhibitory concentrations of β-lactam induction. The increasing expression of lpl by β-lactams was directly controlled by the global regulator SarA. The β-lactam-induced Lpls stimulated the production of interleukin-6 and tumor necrosis factor alpha in RAW 264.7 macrophages. The lpl deletion mutants (N315Δlpl and USA300Δlpl) decreased the proinflammatory cytokine levels in vitro and in vivo. Purified lipidated SA2275-his proteins could trigger a Toll-like-receptor-2 (TLR2)-dependent immune response in primary mouse bone marrow-derived macrophages and C57BL/6 mice. The bacterial loads of N315Δlpl in the mouse kidney were lower than those of the wild-type N315. The β-lactam-treated MRSA exacerbated cutaneous infections in both BALB/c and C57BL/6 mice, presenting increased lesion size; destroyed skin structure; and easily promoted abscess formation compared with those of the untreated MRSA. However, the size of abscesses caused by the β-lactam-treated N315 was negligibly different from those caused by the untreated N315Δlpl in C57BL/6 TLR2−/− mice. Our findings suggest that β-lactams must be used carefully because they might aggravate the outcome of MRSA infection compared to inaction in treatment. IMPORTANCE β-Lactam antibiotics are widely applied to treat infectious diseases. However, certain poor disease outcomes caused by β-lactams remain poorly understood. In this study, we have identified a cluster of lipoprotein-like genes (lpl, sa2275–sa2273) that is upregulated in the major clinically prevalent MRSA clones in response to subinhibitory concentrations of β-lactam induction. The major highlight of this work is that β-lactams stimulate the expression of SarA, which directly binds to the lpl cluster promoter region and upregulates lpl expression in MRSA. Deletion of lpl significantly decreases proinflammatory cytokine levels in vitro and in vivo. The β-lactam-induced Lpls enhance host inflammatory responses by triggering the Toll-like-receptor-2-mediated expressions of interleukin-6 and tumor necrosis factor alpha. The β-lactam-induced Lpls are important virulence factors that enhance MRSA pathogenicity. These data elucidate that subinhibitory concentrations of β-lactams can exacerbate the outcomes of MRSA infection through induction of lpl controlled by the global regulator SarA.